2021
DOI: 10.3844/sgamrsp.2021.41.67
|View full text |Cite
|
Sign up to set email alerts
|

Seismic and Thermal Retrofitting of Masonry Buildings with Fiber Reinforced Composite Systems: A State of the Art Review

Abstract: Old masonry buildings represent the largest part of traditional constructions. Generally, they are both seismically vulnerable and thermally dispersive. Therefore, the need for seismic and thermal retrofitting aimed at reducing their vulnerability and environmental impact has motivated research efforts towards sustainable retrofitting solutions. This study presents a literature review of the approaches currently available for masonry retrofitting. Specifically, it highlights the use of fiber in textile form i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 81 publications
(147 reference statements)
0
7
0
Order By: Relevance
“…Among all possible actions, the insulation of new and existing buildings plays a key role, since it is well known that good thermal insulation of the building could lead to saving about 65% of the energy consumption [12][13][14][15]. As highlighted in [16,17], most of the insulating materials are made mainly from natural and man-made synthetic (organic and inorganic) fibers and several studies have investigated the thermo-physical properties of such materials. Their "best" thermal conductivity was found to range from 0.015 W/(m•K) for aerogel panels to 0.100 W/(m•K) for recycled rubbers, as also shown in [18] and [19].…”
Section: Introductionmentioning
confidence: 99%
“…Among all possible actions, the insulation of new and existing buildings plays a key role, since it is well known that good thermal insulation of the building could lead to saving about 65% of the energy consumption [12][13][14][15]. As highlighted in [16,17], most of the insulating materials are made mainly from natural and man-made synthetic (organic and inorganic) fibers and several studies have investigated the thermo-physical properties of such materials. Their "best" thermal conductivity was found to range from 0.015 W/(m•K) for aerogel panels to 0.100 W/(m•K) for recycled rubbers, as also shown in [18] and [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that all the samples were made following scrupulously processing and drying procedures based on the previous experience of the authors in other similar research activities [16], [33] 34] and on specific indications found in the literature [36], [57].…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…Actually, new composite construction materials can be designed to have good thermal insulating property and good structural behavior. This can be obtained using conventional or The use of fibers in construction is getting more and more common, and both man-made and natural fibers are widely used for various purposes [19].…”
Section: Introductionmentioning
confidence: 99%
“…The pros and cons of natural fibers are reported in [19] and based on the most recent data [46], natural fibers (flax, hemp, jute or kenaf) have 78%-79.4% lower carbon footprint, when compared with glass or mineral fibers.…”
Section: Introductionmentioning
confidence: 99%